Burnout experienced by South African novice occupational therapists - Bruce, Morgann Moira (My University, 2021)
International studies have found that burnout exists among occupational therapists. While most South African research has focused on medical doctors, sparse research has focused on occupational therapists. There is anecdotal evidence that high levels of burnout exist especially now during the COVID-19 pandemic, but there is minimal research about the extent, nature and causative factors of burnout in novice occupational therapists within the South African context. Empirical evidence is needed to understand the South African occupational therapy population's burnout levels to put in place policies both at a university and work environment level to mitigate and manage burnout, particularly in novice professionals. Aim: This study aimed to explore the domains of burnout in novice South African occupational therapists and explore if work-life factors play a role in burnout. Methods: This study followed a descriptive quantitative, cross-sectional, survey design. In early 2020 (March to June), in the height of South Africa’s national lockdown due to the coronavirus pandemic, a single survey consisting of: a demographic questionnaire, Maslach Burnout Inventory – Human Services Survey, and Areas of Worklife Survey, was sent to South African occupational therapists electronically using REDcap. Using an exponential non-discriminative convenience snowballing sampling method, 261 participants completed all three questionnaires. The data obtained were then used for exploratory analysis. Result: High levels of emotional exhaustion and depersonalisation were found in 78.54% and 49.04% of participants, respectively. Simultaneously, 60.15% of participants indicated a high level of personal accomplishment with their workplace. Workload accounted for 25% of the variance in emotional exhaustion, and 36.78% of participants reported a high workload indicating a mismatch between themselves and their workplace. Conclusion: In this study, the novice South Africa occupational therapists were found to have a higher level of Emotional Exhaustion, Depersonalisation and Personal Accomplishment than the normative data found in the fourth edition of the MBI manual and international occupational therapy studies. Participant’s workload was the only area from the Areas of Work-life Survey on the job-persons fit mismatch end of the scale. Therefore, human resource departments would be wise to implement workload balance strategies within their work environments to prevent burnout from occurring in their employees.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021